Morphology-controlled synthesis of ZnSnO3 hollow spheres and their n-butanol gas-sensing performance - Feng, Guoqing; Che, Yanhan; Song, Chengwen; Xiao, Jingkun; Fan, Xinfei; Sun, Shuang; Huang, Guohui; Ma, Yanchao (Ceramics international, 2021)
ZnSnO3 hollow spheres were successfully synthesized via a mild hydrothermal strategy followed by an annealing process. Their microstructures, morphologies and chemical compositions were characterized by a variety of techniques, including X-ray diffraction, transmission electron microscopy and N2 adsorption-desorption. Due to rapid co-precipitation and self-assembly, a resultant hollowing process was achieved, and ZnSnO3 particles were reorganized into hollow structures. Furthermore, the possible formation mechanism was interpreted by means of several experiments under different reaction conditions. The as-fabricated ZnSnO3 sensors with hollow interiors and permeable surfaces were investigated with six volatile gases, which exhibited fast response and high selectivity to n-butanol at the much-lowered optimal temperature of 200 °C. In particular, the response time of the sensors based on ZnSnO3 hollow spheres was 3 s, implying that they are a potential candidate for n-butanol gas detection. In addition, the gas-sensing mechanism of the ZnSnO3 sensor was also investigated.